Players, bumps & cocktail sausages - Preston, Natasha (2014)
"Putting his player ways behind him, Jasper Dane is now strictly a one-woman man. Jasper, desperate to start a family with his wife, Abby, is devastated when she puts their baby plans on hold. Holly has just arrived in town for the summer, and after landing a job with Jasper, the two form an unlikely friendship. Abby's immediate dislike of Holly and Jasper spending time together causes him to question her fidelity. Broken hearted at Abby's sudden change of heart, and suspicious for her reasons, Jasper takes action, sparking a chain of events that makes his once well planned life spiral out of control."--Back cover.
Keywords: Man-woman relationships -- Fiction; Adultery -- Fiction; Life change events -- Fiction